An Observational Study to Evaluate the Safety and Efficacy of Telbivudine in Adults with Chronic Hepatitis B - Ali Sulaiman; Laurentius A Lesmana; Nafrialdi Nafrialdi; Helyanna Helyanna (Acta Medica Indonesiana)
Aim: to assess the safety and efficacy of telbivudine therapy in adult patients with CHB in Indonesia. Methods: the study design was prospective cohort study. Multicenter study of adult CHB patients requiring oral antiviral therapy in daily practice setting. All patients received 600 mg of telbivudine daily for one year. Recruitment and decision to start telbivudine therapy was based on clinical indication as assessed by the participating physicians. The primary end-point was patient safety (adverse event or serious adverse events); while the secondary end-points were HBeAg seroconversion, changes of serum HBV DNA levels and serum ALT normalization. Patients were assessed at week-24 and week-52 of treatment. Results: a total of 176 cases were eligible for analysis, comprising 104 (59.8%) HBeAg-positive and 70 (40.2%) HBeAg-negative patients. Adverse events were reported in 7 (4.0%) patients, most of them were mild. HBeAg loss and seroconversion rate was 28.8% and 14.14% at week-52 respectively. Undetectable HBV DNA (PCR negativity) was 51.8% at week-24 and 62.7% at week-52. Median HBV DNA levels were significantly reduced from baseline to week-24 and week-52 treatment (both p<0.001; Wilcoxon’s signed-rank test). Normalization of serum ALT activity occurred in 85 (73.28%) patients at week-52. Conclusion: Telbivudine therapy is generally safe and well tolerated among adult Indonesian patients with chronic hepatitis B. Treatment efficacy in terms of HBeAg loss and seroconversion, changes of HBV DNA levels and serum ALT normalization were similar to previous reported studies.